2016
DOI: 10.1177/1065912916670272
|View full text |Cite
|
Sign up to set email alerts
|

Communication Technology and Reports on Political Violence

Abstract: The spread of internet and mobile phone access around the world has implications for both the processes of contentious politics and subsequent reporting of protest, terrorism, and war. In this paper, we explore whether political violent events that occur close to modern communication networks are systematically better reported than others. Our analysis approximates information availability by the level of detail provided about the date of each political violent event in Africa 2008-2010 and find that while acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…These results make clear that media coverage is not uniform across space, but highly dependent on demand for and access to information. Previous studies of media bias have drawn similar conclusions within conflicts (Croicu and Kreutz 2017;Weidmann 2015), but our results suggest that future work should pay more attention to cross-national differences in reporting quality.…”
Section: Concluding Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results make clear that media coverage is not uniform across space, but highly dependent on demand for and access to information. Previous studies of media bias have drawn similar conclusions within conflicts (Croicu and Kreutz 2017;Weidmann 2015), but our results suggest that future work should pay more attention to cross-national differences in reporting quality.…”
Section: Concluding Discussionsupporting
confidence: 80%
“…These approaches do not, however, correct for systematic bias in which events are likely to be underreported in the first place. Previous research has found that media reporting of violence is positively correlated with the presence of communications technology (Croicu and Kreutz 2017; Weidmann 2016) and regime type (Baum and Zhukov 2015), while findings for press freedom (Drakos and Gofas 2006;Urlacher 2009), severity of violence (Croicu and Kreutz 2017; Davenport and Ball 2002; Price and Ball 2014) and urban areas (Croicu and Kreutz 2017;Davenport and Ball 2002) are mixed. Media reporting also varies by country: African countries are often excluded from international relations research because of cross-national differences in information availability (Lemke 2003, 120-124).…”
Section: How Events Become Newsmentioning
confidence: 96%